Formulation of Fuzzy Correlated System for Node Behavior Detection in WSN - Shahidah, Noor; Azni, A. H (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
Wireless Sensor Network depends highly upon the cooperation among the nodes behavior in transmission of packet data, messages and route discovery. Over open medium environment, nodes are free to move and may change their behavior arbitrarily. In the presence of misbehavior node in some cases, it may instigate its neighboring nodes to compromise with the misbehaved node. Thus, this has resulted to a spreading of correlated node behavior and the impact of this event may result in high severity in network performance. Therefore, fuzzy logic model is proposed to formulate the correlated node behavior in WSN. The formulation of correlated node behavior based on fuzzy logic function of peer nodes real parameter measurement is investigated to determine the status of the node and then the fuzzy neural network will model the correlated node behavior occurrence. The accuracy of the results is established via sensor network simulation. The result of this study is providing a fundamental guideline for network designer in order to understand the fault-tolerance in network topology.